1992
DOI: 10.1152/jappl.1992.72.1.121
|View full text |Cite
|
Sign up to set email alerts
|

A model of dynamic exercise: the decerebrate rat locomotor preparation

Abstract: The purpose of this study was to develop a dynamic exercise model in the rat that could be used to study central nervous system control of the cardiovascular system. Rats of both sexes were decerebrated under halothane anesthesia and prepared for induced locomotion on a freely turning wheel. Electrical stimulation of the mesencephalic locomotor region (MLR) elicited locomotion at different speeds and gait patterns and increased heart rate and blood pressure. Two maneuvers were performed to illustrate the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 15 publications
1
53
0
Order By: Relevance
“…This stimulation also evoked both left and right tibial nerve discharges supplying triceps surae muscles after muscle paralysis. These data were consistent with previous studies by others (5,9,28,43,50).…”
Section: Methodssupporting
confidence: 94%
See 2 more Smart Citations
“…This stimulation also evoked both left and right tibial nerve discharges supplying triceps surae muscles after muscle paralysis. These data were consistent with previous studies by others (5,9,28,43,50).…”
Section: Methodssupporting
confidence: 94%
“…Stimulating the MLR in paralyzed animals has been extensively used to study the physiological roles played by central command (5,7,14,21,28,43). However, in this experimental preparation, it is difficult to equate the MLR stimulation with the way that this site is activated as central command during actual exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,24,25 Our findings indicate that tonic and reflex cardiovascular adjustments are also evoked from the PPT via direct cholinergic projections to the RVLM. These data support our hypothesis that cholinergic input to the RVLM is involved in central command.…”
Section: Padley Et Al Cholinergic Inputs To Rvlm In Central Commandmentioning
confidence: 63%
“…Previous studies have shown that the PPT is involved in initiation of movement and modulation of muscle tone during locomotion, exercise, and arousal. 4,24,25 Additionally, the PPT connects albeit indirectly with both motor and sympathetic outflows. 5 We aimed, firstly, to determine the role of the RVLM in the autonomic responses and effects on reflex control of the circulation evoked by central mAChR activation.…”
mentioning
confidence: 99%